GOVERNMENTAL CONTROL ON JURNALISTIC PRACTICE IN 'PSEUDO-DEMOCRATIC' MALAYSIA AND SINGAPORE OR BIG COMPANY CONTROL ON JOURNALISTIC PRACTICE IN 'ESTABLISHED-DEMOCRATIC' AUSTRALIA: WHICH IS WORSE AND WHERE ARE THE PARALLESL - Sinclair, Elizabeth (Faculty of Law, Universitas Brawijaya, 2015)
Amanda Whiting and Timothy Marjoribanks argued in their chapter Media professional's perceptions of defamation and other constraints upon news reporting in Malaysia and Singapore[1]that Malaysia and Singapore experience, due to a number of factors, restricted media freedom - many of these factors relating to the semi-democratic nature of Malaysian and Singaporean government. [1]Amanda Whiting and Timothy Marjoribanks, 'Media Professionals' Perceptions of Defamation and other Constraints upon News Reporting in Malaysia and Singapore' in Andrew Kenyon, Tim Marjoribanks, Amanda Whiting (eds.) Democracy, Media and Law in Malaysia and Singapore (Routledge, London, 2013), 129-156.